ASSOCIATION OF COMPLICATIONS OF DIABETES MELLITUS WITH SOCIODEMOGRAPHIC DETERMINANTS IN PATIENTS PRESENTING TO AYUB TEACHING HOSPITAL ABBOTTABAD - Saqib Malik,; Farhat Naz,; Fatima Iqbal, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Diabetes mellitus is a disease with many possible complications like macrovascular i-e stroke, coronary artery disease, peripheral artery disease, and microvascular i-e retinopathy, neuropathy and nephropathy. Many studies have been done in past to find the frequencies of these complications and their association with sociodemographic determinants of diabetic patients, but there was limited data available in our setup. This study was carried out to determine the frequency of micro and macrovascular complications of diabetic patients and their association with socioeconomic determinants at Ayub Teaching Hospital, Abbottabad. Methods: This cross-sectional study was carried out at Ayub Teaching Hospital, Abbottabad, Pakistan, from July 2022 till December 2023 on 113 diabetic patients. The data was collected on micro and macrovascular complications of diabetes on a pre-designed structured proforma and analyzed by means of SPSS-23. Results: The most common macrovascular complication was coronary artery disease 10(8.8%) while neuropathy 35(31%) was the most common microvascular complication. Among macrovascular complications stroke was associated significantly with age (p=0.01) and duration of diabetes (p=0.032). Among microvascular complications neuropathy was associated with gender (p=0.047), nephropathy with smoking (p=0.02) and retinopathy with both gender (p=0.019) and smoking (p=0.017). Conclusion: In this study there was significant association between, gender with neuropathy and retinopathy, smoking with nephropathy and retinopathy, stroke with age and duration of diabetes.